Extensive Simulated Diving Aggravates Endothelial Dysfunction in Male Pro-atherosclerotic ApoE Knockout Rats - Berenji Ardestani, Simin; Matchkov, Vladimir V.; Hansen, Kasper; Jespersen, Nichlas Riise; Pedersen, Michael; Eftedal, Ingrid (Frontiers in Physiology, 2020)
Introduction: The average age of the diving population is rising, and the risk of atherosclerosis and cardiovascular disease in divers are accordingly increasing. It is an open question whether this risk is altered by diving per se. In this study, we examined the effect of 7-weeks simulated diving on endothelial function and mitochondrial respiration in atherosclerosis-prone rats. Methods: 24 male ApoE knockout (KO) rats (9-weeks-old) were fed a Western diet for 8 weeks before 12 rats were exposed to simulated heliox dry-diving in a pressure chamber (600 kPa for 60 min, decompression of 50 kPa/min). In total, the rats dived 14 times twice-weekly for 7 weeks. The remaining 12 non-diving rats served as controls. Endothelial function of the pulmonary and mesenteric arteries was examined in vitro using an isometric myograph. Mitochondrial respiration in cardiac muscle tissues was measured using high-resolution respirometry. Results and conclusion: Both ApoE KO diving and non-diving rats showed changes in endothelial function at the end of the intervention, but the extent of these changes was larger in the diving group. Altered nitric oxide signaling was primarily involved in these changes. Mitochondrial respiration was unaltered. In this pro-atherosclerotic rat model of cardiovascular changes, extensive diving appeared to aggravate endothelial dysfunction rather than promote adaptation to oxidative stress.